Elevational patterns and seasonal baseline of bird diversity in the Lomas de Atiquipa, Southern Peru - CESAR R. LUQUE-FERNANDEZ; LUIS N. VILLEGAS-PAREDES (Society for Indonesian Biodiversity, 2026)
Abstract. Luque-Fernandez CR, Villegas-Paredes LN. 2026. Elevational patterns and seasonal baseline of bird diversity in the Lomas de Atiquipa, Southern Peru. Biodiversitas 27 (6): d270603. https://doi.org/10.13057/biodiv/d270603. Coastal lomas are fog-dependent vegetation oases in the South Pacific desert, where wet-dry seasonality influences vegetation cover and habitat availability. We characterized bird diversity in the Lomas de Atiquipa, southern Peru, and evaluated its variation along elevation, habitat types, and seasons. We integrated historical records compiled between 2002 and 2018 with standardized surveys conducted in 2018 during the dry and wet seasons. Historical records were used to describe the local avifaunal inventory and broad richness patterns across 100-m elevational bands and habitat types, whereas the standardized surveys were used to evaluate habitat- and season-related variation in community structure based on observed counts. We recorded 110 species belonging to 17 orders and 41 families, including four Peruvian endemics. The highest compiled richness was recorded at mid elevations, particularly between 600 and 700 m asl (55 species), and in open forest, agricultural areas, and herbaceous-shrub habitat. Community composition in the standardized 2018 surveys differed significantly among habitats (ANOSIM R: 0.633, P: 0.003), whereas the overall separation between dry and wet seasons was weak and not significant (R: 0.052, P: 0.258). Although mean Bray-Curtis dissimilarity between seasons was high (78.6%), this reflected shifts in the relative contribution of species within the system rather than a consistent wet-vs-dry grouping of samples. These results identify the mid-elevation fog belt and its habitat mosaic as an evidence-based priority for future monitoring and conservation management in Atiquipa.